Killing England [compact disc, unabridged] : the brutal struggle for American independence - O'Reilly, Bill; Dugard, Martin (Macmillan Audio, 2017)
Told through the eyes of George Washington, Benjamin Franklin, Thomas Jefferson, and Great Britain's King George III, O'Reilly and Dugard chronicle the path to independence in gripping detail, taking the listener from the battlefields of America to the royal courts of Europe. They recreate the wars landmark battles, including Bunker Hill, Long Island, Saratoga, and Yorktown, revealing the savagery of hand-to-hand combat and the often brutal conditions under which these brave American soldiers lived and fought.